Challenges and Opportunities of E-Learning for Women's Education in Developing Countries: Insights from Women Online University - Hakimi, Nargis; Hakimi, Musawer; Hejran, Muska; Quraishi, Tamanna; Qasemi, Parisa; Ahmadi, Lima; Daudzai, Mehriya; Ulusi, Helena (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
This case study explores the challenges and opportunities of e-learning for women's education in developing countries, focusing on the experience of Women Online University. The purpose is to assess the impact of e-learning on women's empowerment and socio-economic advancement, examining factors influencing engagement with e-learning platforms. The study involved 220 female students across various faculties and age groups, utilizing surveys and statistical analysis to evaluate e-learning effectiveness. Results indicate a positive perception of e-learning, with significant relationships between e-learning contribution, empowerment, and socio-economic advancement. Access to technology is influenced by digital literacy, age, and faculty of study. In conclusion, the study highlights the transformative potential of e-learning for women's education, emphasizing the importance of addressing digital literacy gaps and enhancing institutional support. Recommendations include leveraging innovative pedagogical strategies to optimize e-learning outcomes and promote gender equality in education. This case study contributes valuable insights into the role of e-learning in empowering women in developing countries, informing future research and policy initiatives in educational development and gender equality efforts.